2019
DOI: 10.1002/casp.2398
|View full text |Cite
|
Sign up to set email alerts
|

Community psychology, digital technology, and loss: Remembrance activities of young adults who have experienced the death of a close friend

Abstract: We argue for community psychology to include digital communications technology in research on ways that the social environment shapes fundamental human experiences. We present a qualitative study that examined the narrative accounts of 20 young adults who experienced the death of a close friend to describe both traditional and digital forms of remembrance in coping with loss. Findings suggest that young adults' activities both online and offline were intended to acknowledge the loss, exchange social support, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Despite widespread social media participation in the US and other countries, studies of online communities continue to be underrepresented in community psychology research. Stein et al (2019) found a total of 15 articles related to online communities in their informal review of three major community psychology journals. Similarly, Steltenpohl, Reed, and Keys (2020) found only 23 articles of any type published in journals relevant to community psychology between 1997 and 2018 related to online communities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite widespread social media participation in the US and other countries, studies of online communities continue to be underrepresented in community psychology research. Stein et al (2019) found a total of 15 articles related to online communities in their informal review of three major community psychology journals. Similarly, Steltenpohl, Reed, and Keys (2020) found only 23 articles of any type published in journals relevant to community psychology between 1997 and 2018 related to online communities.…”
Section: Introductionmentioning
confidence: 99%
“…Social media has also had a dramatic influence on citizen participation and the pursuit of social justice (Li et al, 2020) which are fundamental issues in community psychology research. The call for increased attention in community psychology to social media is compelling given the values and goals of our discipline surrounding the pursuit of social justice and the distribution of power and resources in society (Stein et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…While there are numerous reasons why patients would take their lives on or near key dates, it is possible that seeing a social media ‘memory’, a feature that shows content that users had generated or had been tagged in on a certain date, can trigger overwhelming or negative feelings. 31 However, this warrants further study.…”
Section: Discussionmentioning
confidence: 89%
“…This approach encourages the intervention of professionals on different levels —one of which is the online social network that is widely used by the youth and adolescent community (Faelens et al, 2021). As a discipline, community psychology has much to offer in the study of how virtual social contexts, such as social networks, contribute to positive social change, health, and well‐being (Stein et al, 2019). It is therefore relevant to include virtual contexts in the promotion of individual and community well‐being, using these tools both for preventive purposes, to identify at‐risk individuals, and to provide timely information and foster social support online (Brown, Fischer, Goldwich, & Plener, 2020).…”
Section: Instagram As An Online Community For Psychologists' Interven...mentioning
confidence: 99%